The Effectiveness of the Creative Dimension of P5 (Entrepreneurship Theme) on Elementary School Students’ Financial Literacy Skills - Nelinda Oktarina; Susanti Faipri Selegi; Sri Wahyuningsih (ELRISPESWIL - Lembaga Riset dan Pengembangan Sumberdaya Wilayah, 2026)
This study aims to analyze the effectiveness of implementing the creative dimension within the Projek Penguatan Profil Pelajar Pancasila (P5) under the entrepreneurship theme in improving elementary school students’ financial literacy skills. The study employed a quantitative approach using a quasi-experimental nonequivalent control group design. The sample consisted of 55 fifth-grade students from SD Negeri 128 Palembang, divided into an experimental group (27 students) and a control group (28 students). The experimental group received treatment through P5 entrepreneurship-based activities emphasizing the creative dimension, including product idea planning, simple product development, pricing and capital simulation, and contextual selling practices, while the control group followed conventional instruction. Data were collected using a financial literacy test, observation, and documentation, and analyzed through normality tests, homogeneity tests, and an independent samples t-test on posttest scores. The results revealed a significant difference between the two groups, with t(53) = -8.664; p < 0.001, where the experimental group (M = 85.19) outperformed the control group (M = 80.71). The effect size was also found to be strong (Cohen’s d = 2.34), indicating a substantial impact of the intervention. These findings suggest that integrating the creative dimension within P5 entrepreneurship activities is highly effective in enhancing students’ financial literacy skills and provides meaningful, contextual learning experiences in elementary education.